تأثير الإدارة الخضراء في ظل التغيرات التكنولوجية على النمو الاقتصادي: دراسة قياسية على دول شمال أفريقيا - عبدالعال، هبة الله سمير محمد; محمد، ياسمين عبدالرحيم سيد أحمد (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2025)
Green management, when adopted in conjunction with technological change, can have a significant and positive impact on economic growth in North African countries. this region, which faces significant environmental challenges, can benefit greatly from the combination of environmental sustainability and modern technology to achieve sustainable economic growth. below is an analysis of the impact of green management with technological change on economic growth. the study data is represented by the cross-section data, which is represented by the North African countries (Egypt, Tunisia, Algeria, Morocco), and the time-series data for the period (1990:2020) annual data. previous studies and an in-depth review of the literature identified the variables that represent green management and its impact in supporting economic growth. the per capita share of the gross domestic product was the dependent variable reflects the variable that expresses economic growth, and the independent variables reflect green management in light of technological changes (the percentage of technology use in the business environment, the volume of carbon dioxide emissions, the environmental comparative advantage related to technology, the percentage of renewable energy use from the total energy). one of the most important recommendations of the study is the need to adopt clean technology, as North African countries must invest in environmentally friendly technology such as renewable energy (solar and wind energy), water and energy efficiency, developing modern and sustainable irrigation systems, and spreading awareness of the importance of environmental management and green technologies through educational and training programs in the field of green management and environmental technologies, as well as encouraging environmentally friendly behaviors among citizens and institutions. الإدارة الخضراء، عندما يتم تبنيها جنبا إلى جنب مع التغيرات التكنولوجية، يمكن أن يكون لها تأثير كبير وإيجابي على النمو الاقتصادي في دول شمال إفريقيا. هذه المنطقة التي تواجه تحديات بيئية كبيرة، يمكن أن تستفيد بشكل كبير من الدمج بين الاستدامة البيئية والتكنولوجيا الحديثة لتحقيق نمو اقتصادي مستدام. وفيما يلي تحليل لتأثير الإدارة الخضراء مع التغيرات التكنولوجية على النمو الاقتصادي. تتمثل بيانات الدراسة في بيانات القطاع العرضي (Cross-section) والتي تتمثل في دول شمال أفريقيا (مصر، تونس، الجزائر، المغرب)، وبيانات السلسة الزمنية (Time-series) للفترة (1990: 2020) بيانات سنوية، حددت الدراسات السابقة والمراجعة المتعمقة للأدبيات للمتغيرات التي تمثل الإدارة الخضراء وأثرها في دعم النمو الاقتصادي، وكان نصيب الفرد من الناتج المحلي الإجمالي يعكس (المتغير التابع) وهو المتغير الذي يعبر عن النمو الاقتصادي، والمتغيرات المستقلة التي تعكس الإدارة الخضراء في ظل التغييرات التكنولوجية (نسبة استخدام التكنولوجيا في بيئة الأعمال، حجم انبعاثات غاز ثاني أكسيد الكربون، الميزة النسبية البيئية المتعلقة بالتكنولوجيا، نسبة استخدام الطاقة المتجددة من إجمالي الطاقة). ومن أهم توصيات الدراسة يتوجب تبني التكنولوجيا النظيفة حيث يجب على دول شمال إفريقيا، الاستثمار في التكنولوجيا الصديقة للبيئة مثل الطاقة المتجددة (الطاقة الشمسية والرياح)، والكفاءة في استهلاك المياه والطاقة، وتطوير أنظمة الري الحديثة والمستدامة، ونشر الوعي بأهمية الإدارة البيئية والتكنولوجيات الخضراء من خلال برامج تعليمية وتدريبية في مجال الإدارة الخضراء والتقنيات البيئية، وكذلك التشجيع على السلوكيات الصديقة للبيئة بين المواطنين والمؤسسات.